VALIDITY OF TIME TO EXHAUSTION ON A FIXED INCREMENTAL TREADMILL PROTOCOL AS A MEASURE OF AEROBIC FITNESS IN 10-YEAR OLD CHILDREN - Eivind Aadland; Turid Skrede; Asgeir Mamen; Geir Kåre Resaland (Sport Scientific And Practical Aspects, 2025)
Purpose: High aerobic fitness is important for children’s metabolic health. Direct measurement of peak oxygen consumption (VO 2peak) is often not feasible, but time to exhaustion (TTE) on a fixed incremental treadmill protocol has been used as a measure of aerobic fitness. The aim of the present study was to determine the validity of TTE as a measure of VO 2peak in 10-year old children. Methods: A total of 118 10-year old children (67 boys and 51 girls) were recruited from one school and performed an incremental VO 2peak-test where oxygen consumption and TTE were assessed. Of these, 113 children provided valid data and served as subjects for the analysis of validity, which was performed using linear regression analysis. Results The equation to estimate VO 2peak was: VO2peak= (coefficient(95% bootstrapped confidence interval)) 26.909 (12.910 to 40.879) + 0.063(0.048 to 0.079) · TTE – 3.225 (-5.391 to -1.000)·gender - 0.330 (-0.460 to -0.196)· body mass (R 2 = 0.72, SEE = 4.82, p < .001). Conclusions Time to exhaustion yielded valid estimates of VO 2peak for 10-year old children. However, researchers should be aware of the amount of noise in indirect tests to estimate aerobic fitness. Future studies should assess reliability and external validity to determine if the current findings are reproducible and valid across different contexts.